2021
DOI: 10.1021/acssuschemeng.0c09353
|View full text |Cite
|
Sign up to set email alerts
|

Hydrothermal Reduction of NaHCO3 into Formate with Protein-Based Biomass over Pd/γ-Al2O3 Nanocatalysts

Abstract: CO2/HCO3 – reduction with a renewable reductant has a promising potential for tackling the CO2 problem, but achieving high efficiency is still a challenge. Herein, protein-based biomass as the renewable reductant is found to achieve efficient NaHCO3 reduction under hydrothermal conditions. With the Pd/γ-Al2O3 nanocatalyst, the efficiency of NaHCO3 reduction reached 49.0% with l-alanine (the model compound of protein) as the reductant, which was attributed to the superior hydrogen activation property of Pd and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 53 publications
0
15
0
Order By: Relevance
“…Yang et al 61 found the yield of formic acid always maintained at ~7% even the water filling ratio raised to 45% when using 2‐pyrrolidone as a reductant. The same phenomenon also occurred when amino‐based reductant L‐alanine was used to generate formic acid from hydrothermal CO 2 reduction , in which the formic acid yield is near ~45% even though Pt/γ‐Al 2 O 3 was added to promote this process 62 …”
Section: Effects Of Reaction Variablesmentioning
confidence: 75%
See 3 more Smart Citations
“…Yang et al 61 found the yield of formic acid always maintained at ~7% even the water filling ratio raised to 45% when using 2‐pyrrolidone as a reductant. The same phenomenon also occurred when amino‐based reductant L‐alanine was used to generate formic acid from hydrothermal CO 2 reduction , in which the formic acid yield is near ~45% even though Pt/γ‐Al 2 O 3 was added to promote this process 62 …”
Section: Effects Of Reaction Variablesmentioning
confidence: 75%
“…Moreover, they found that substitutional groups on −NH 2 oxidation could have a steric effect on the production of formate from HCO 3 − . 62 The benzene containing amino-based substance like L-lysine had a weaker ability for HCO 3 − reduction with only 19.2% yield of formate, which was even less than a half of the yield (51.2%) with glycine as reductant. DFT calculation revealed that the steric hindrance had a negative impact on the dehydrogenation of the amino group, in which 2.53 eV energy barrier for rate-determining step of L-lysine was required that is significantly higher than the value of 1.5 eV for glycine.…”
Section: Hydrothermal Reduction Of Co 2 To Formic Acid With Biomass-d...mentioning
confidence: 98%
See 2 more Smart Citations
“…showed that protein‐based microalgae could also reduce CO 2 emissions, and the microalgae themselves could be converted into value‐added chemicals, such as organic acids and N‐substituted lactams. Utilizing the nitrogen source in protein‐based biomass can also reduce the consumption of fossil fuels [13] . Therefore, it is of great significance to study the use of nitrogen‐rich natural microalgae to produce value‐added nitrogen‐containing compounds [1c,14] .…”
Section: Introductionmentioning
confidence: 99%